2011
DOI: 10.1111/j.1540-8191.2011.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Circumflex Coronary Aneurysm with Fistulous Connection to Coronary Sinus Associated with Persistent Left Superior Vena Cava

Abstract: Circumflex coronary arteriovenous fistula associated with aneurysmal dilatation and draining into coronary sinus (CS) is rare. A 57-year-old female presented with progressive dyspnea and was found to have a tortuous multiloculated aneurysm of the circumflex coronary artery terminating into the CS associated with a persistent left superior vena cava. The operative repair and management of coronary arteriovenous fistula are the subject of this case report and review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Dyspnea on exertion is one of the commonest symptoms of patients with coronary artery fistulas (13), although coronary artery fistulas are usually asymptomatic (14). Rittenhouse et al reported that surgical correction may be considered for coronary artery fistula when the Qp/Qs ratio is 2.0 or greater (15).…”
Section: Discussionmentioning
confidence: 99%
“…Dyspnea on exertion is one of the commonest symptoms of patients with coronary artery fistulas (13), although coronary artery fistulas are usually asymptomatic (14). Rittenhouse et al reported that surgical correction may be considered for coronary artery fistula when the Qp/Qs ratio is 2.0 or greater (15).…”
Section: Discussionmentioning
confidence: 99%
“…There are no consistent guidelines for treatment as these fistulas have variable sizes and anatomical variants. However, it is well established that ischemic symptoms, significant shunt (Qp/Qs>1.5 regardless of symptoms), and the associated aneurysmal dilatation are indications for treatment 6-8). Therefore, due to the patient's complaints of exertional dyspnea and a Qp/Qs>1.5, our patient was deemed to be in need of treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Two treatment modalities are available for fistula closure: surgical or percutaneous TCC. The first successful surgical closure was reported by Björk and Carfoord in 1947,1)9) whereas the first therapeutic embolization was performed in 1974 by Zuberbuhler et al10) The treatment modality that was used depends on the age of the patient, the morphology and the size of the fistula, as well as the presence or absence of an associated heart disease 6). Surgical closure by epicardial and endocardial ligation is the gold standard in the treatment of CAF, and remains as a safe and effective procedure with good reported rates of success 8).…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment options for CAFs vary and include surgical ligation alone, surgical ligation with coronary artery bypass surgery, or transcatheter closure [Chowdhury 2009]. Surgical closure can be performed using different techniques [Chowdhury 2009;Darwazah 2011;Nakayama 2011]. Proximal-type CAF (type A) can be treated by epicardial ligation maintaining normal flow, and distal-type CAF (type B) requires termination of the fistula flow by an intracardiac purse-string suture via cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%